Low-carbon optimization planning method for integrated energy system based on DG uncertainty affine model - JIANG Tao; XU Cong; JIA Shaohui; WANG Shen; ZHANG Yajian (Dianxin kexue)
Aiming at the problem that the output of distributed generators (DG) of new energy sources such as wind power and photovoltaic is uncertain due to changes in environmental factors, and the transaction price of the existing carbon trading model is fixed, resulting in increased carbon reduction costs, an integrated energy system optimization planning method that takes into account dynamic carbon emission constraints and DG uncertainty was proposed. Firstly, a DG output model based on matrix affine algorithm was established according to environmental conditions to reduce the impact of DG output uncertainty on the optimization planning of the integrated energy system. Secondly, carbon emissions was introduced as a punitive measure into the optimization planning of the integrated energy system to improve the traditional carbon trading model and reduce the carbon emissions of the integrated energy system. Then, based on the differential evolution-particle swarm optimization algorithm, the established low-carbon planning model of the integrated energy system was solved to avoid the algorithm from falling into local optimality during the optimization process. Finally, the simulation results on an IEEE 33 node system show that the proposed planning method reduces the total investment cost by 8.68% and 2.93% respectively compared with the traditional stochastic optimization and interval optimization planning methods. Compared with the traditional fixed carbon trading price model, carbon emissions are reduced by 6.28%.